THE PRESS AND PUBLIC OVERSIGHT IN THE FIRST QUARTER-CENTURY OF UZBEKISTAN’S INDEPENDENT DEVELOPMENT: EVOLUTION AND PRACTICE (Eureka Journal of Humanities and Social Research, 2026)
This article examines, from a historical-analytical perspective, the formation of the press system and the evolution of the institutional foundations of public oversight during the first quarter-century of Uzbekistan’s period of independent development (1991–2016). The legal-historical content of the original “Law on Mass Media” adopted in 1991, the revisions of 1997 and 2007, as well as the 2014 “Law on the Openness of Activity of the Bodies of State Power and Administration” is subjected to detailed analysis. The article likewise discusses the divergence between de jure (legislation) and de facto (practice), the indicators produced by international organizations such as Reporters Without Borders and Freedom House, and the manner in which the legacy of this first quarter-century is being reinterpreted within the post-2017 reform stage.
Keywords: Press, public oversight, mass media, independence, censorship, openness of information, civil society, Constitution, informatization, digital press.